BIODIVERSITY OF HYMENOPTERAN PARASITOIDS ON CERTAIN INSECT PESTS OF CROPS IN MANIPUR - SUBHARANI, S.; SINGH, T. K.; SINGH, P. MUNAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The systematic survey of hymenopteran parasitoids on certain insect pests of crops in different localities of Manipur varying in altitudes and seasons during 2003-2005 revealed the occurrence of 36 (thirty six) species of parasitoids belonging to the families Aphididae, Chalcidae, Ichneumonidae and Braconidae. Of these, the family Aphididae included the maximum number of the parasitoid species. Among the parasitoids recorded 15 were polyphagous, 02 were oligophagous and 19 were species specific. Their period of occurrence varied depending upon the availability of the host insects as well as the host plants. From the study it also revealed that the maximum species abundance exist bet Ween 601 - 1200mm MSL.